2020
DOI: 10.1039/d0cc03553j
|View full text |Cite
|
Sign up to set email alerts
|

Field-based rational design of p300 histone acetyltransferase inhibitor and systematic evaluation as an anti-fibrotic agent

Abstract: (E)-3-(3-(4-((3-Carbamoylbenzyl)oxy)-3-iodo-5-methoxyphenyl) acryloyl)benzamide (A6) was found as a potent p300 inhibitor (IC50 = 870 nM) showing a similar binding mode to that of acetyl-CoA, a p300 substrate and effective anti-fibrotic activity...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…49 Alternatively, it can regulate histone acetylation directly, modifying the accessibility of promotor regions to transcription factors. 50 In the current experiments, an increase in H3KAc and H4KAC in the promoter of CCN2 tracked with the concomitant induction of this gene, whereas a reduction in the acetylation levels of these histones in the MMP9 gene promoter tracked with a reduction in the levels of expression of this transcript. The clinical significance of these results stands alone because they are an indication of the possibility of using histone acetyltransferase inhibitors to treat fibrosis.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…49 Alternatively, it can regulate histone acetylation directly, modifying the accessibility of promotor regions to transcription factors. 50 In the current experiments, an increase in H3KAc and H4KAC in the promoter of CCN2 tracked with the concomitant induction of this gene, whereas a reduction in the acetylation levels of these histones in the MMP9 gene promoter tracked with a reduction in the levels of expression of this transcript. The clinical significance of these results stands alone because they are an indication of the possibility of using histone acetyltransferase inhibitors to treat fibrosis.…”
Section: Discussionsupporting
confidence: 48%
“…Although, to date, no histone deacetylase inhibitor has reached US Food and Drug Administration approval status, recent evidence provides proof for this concept by showing that a selective p300 inhibitor can ameliorate fibrosis in a bleomycininduced model. 50 Similarly, plumbagin, which was shown to be an inhibitor of p300, suppresses fibrosis in an idiopathic pulmonary fibrosis model. 51 However, these data do not support a role of steroids, specifically triamcinolone, in counterregulating the effects of TGF-b1 by impacting the histone epigenome.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that binding to acetyl-CoA, a p300 substrate, was comparable between A6 and a conventional p300 inhibitor, C646 ( 26 ). Furthermore, A6 demonstrated anti-fibrotic activity in TGF-β1-stimulated lung fibroblasts and in bleomycin-induced murine lung fibrosis in vivo .…”
Section: Resultsmentioning
confidence: 98%
“…Because of the significant inhibitory potency, they performed a preliminary characterization of this chalcone derivative as an anti-fibrotic agent in both TGF-β1-stimulated lung fibroblasts and bleomycin-induced in vivo lung fibrosis mice. Delightfully, based on the obtained findings, the chalcone derivative should represent a good starting point for developing anti-fibrotic drugs ( Hwang et al, 2020 ).…”
Section: Biocatalysismentioning
confidence: 99%